2012
DOI: 10.1089/vbz.2011.0850
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Major Bovine-Associated Zoonotic Infectious Diseases in the Lao People's Democratic Republic

Abstract: Bovine-associated zoonotic infectious diseases pose a significant threat to human health in the Lao People's Democratic Republic (Lao PDR). In all, 905 cattle and buffalo serum samples collected in northern Lao PDR in 2006 were used to determine seroprevalence of five major bovine zoonotic infectious diseases that included Taenia saginata cysticercosis, bovine tuberculosis, Q-fever, bovine brucellosis, and bovine leptospirosis. Five enzyme-linked immunosorbent assays (ELISAs) were used to test for the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 12 publications
3
19
0
Order By: Relevance
“…All three positive cattle sera were tested using the Rose Bengal agglutination test to corroborate the result. The previous study of Vongxay and others19 gave a similar result (i.e., 0.2%). Five sera that were negative according to the cutoff criteria of the ID-Vet ELISA kit that had results close to the cutoff were also tested in the Rose Bengal test, with three of these giving weak positive reactions.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…All three positive cattle sera were tested using the Rose Bengal agglutination test to corroborate the result. The previous study of Vongxay and others19 gave a similar result (i.e., 0.2%). Five sera that were negative according to the cutoff criteria of the ID-Vet ELISA kit that had results close to the cutoff were also tested in the Rose Bengal test, with three of these giving weak positive reactions.…”
supporting
confidence: 80%
“…This may be an epidemiologic significant observation with two of the seropositive villages (Nasarn 33.2%; 2/6 positive and Jomphet 50%; 2/4 positive) having two positive animals in the village (Table 3). In the previous study of Vongxay and others,19 the overall seropositivity was similar (i.e., 4.0%) and Xayaboury Province had a seropositivity rate of 15.9%. Further studies including possible shedding of Coxiella burnetii by using polymerase chain reaction on vaginal swabs and milk in farm animals are required to determine whether Xayaboury Province is indeed an epidemiological hot spot of Q fever activity in Lao PDR.…”
mentioning
confidence: 56%
“…However, a recent slaughterhouse-based study in five northern provinces detected cysticercosis antigen in 52% of cattle and 21% of buffalo. 43 The evidence therefore suggests that taeniasis re-infection was predominantly caused by eating uncooked beef and infection with T. saginata. The two T. solium cases were not associated with knowingly eating uncooked pork and may have arisen simply from inadvertent undercooking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, evidence of bovine tuberculosis were found among buffaloes in Thailand at a high rate (Chanepaiboon et al, 2000) and spatial analysis among dairy herds conducted in Thailand suggests herd-level prevalence of 10% and within herd prevalence of between 10% and 30% (Inchaisri et al, 2003). However, limited study on bovine tuberculosis in the neighboring Laos suggested low prevalence at 1% (Vongxay et al, 2012). No other data can be obtained from other parts of SEA even though efforts of controlling bovine tuberculosis are being actively conducted by many SEA countries veterinary services through test-and-slaughter policy combined with abattoir surveillance (FAO, 2012).…”
Section: Bovine Tuberculosismentioning
confidence: 99%
“…In Laos, the serological surveillance using microscopic agglutination test (MAT) suggested that in cattle the leptospirosis prevalence is 53.6% and in pigs 22.7%, however the clinical impact of the prevalence was not evident. Moreover rice field farmers in Laos have significantly higher exposure to the organism whereby 88.7% were leptospira seropositive as compared to 9.3% in livestock farmer (Kawaguchi et al, 2008;Vongxay et al, 2012). In Malaysia, the work on livestock was performed in mid-1980s by Bahaman et al…”
Section: Leptospirosismentioning
confidence: 99%